Association between Electronic Health Records and Health Care Utilization - Kaushal, R.; Edwards, A.; Kern, L.M.; with the HITEC Investigators (Applied Clinical Informatics, 2015)
Background: The federal government is investing approximately $20 billion in electronic health records (EHRs), in part to address escalating health care costs. However, empirical evidence that provider use of EHRs decreases health care costs is limited.Objective: To determine any association between EHRs and health care utilization.Methods: We conducted a cohort study (2008–2009) in the Hudson Valley, a multi-payer, multi-provider community in New York State. We included 328 primary care physicians in predominantly small practices (median practice size four primary care physicians), who were caring for 223,772 patients. Data from an independent practice association was used to determine adoption of EHRs. Claims data aggregated across five commercial health plans was used to characterize seven types of health care utilization: primary care visits, specialist visits, radiology tests, laboratory tests, emergency department visits, hospital admissions, and readmissions. We used negative binomial regression to determine associations between EHR adoption and each utilization outcome, adjusting for ten physician characteristics.Results: Approximately half (48%) of the physicians were using paper records and half (52%) were using EHRs. For every 100 patients seen by physicians using EHRs, there were 14 fewer specialist visits (adjusted p < 0.01) and 9 fewer radiology tests (adjusted p = 0.01). There were no significant differences in rates of primary care visits, laboratory tests, emergency department visits, hospitalizations or readmissions.Conclusions: Patients of primary care providers who used EHRs were less likely to have specialist visits and radiology tests than patients of primary care providers who did not use EHRs.Citation: Kaushal R, Edwards A, Kern LM, with the HITEC Investigators. Association between electronic health records and health care utilization. Appl Clin Inf 2015; 6: 42–55http://dx.doi.org/10.4338/ACI-2014-10-RA-0089
Keywords: Electronic health records; health services; health utilization; primary health care